2022
DOI: 10.1186/s12933-022-01653-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of coronary microvascular dysfunction assessed by coronary angiography-derived index of microcirculatory resistance in diabetic patients with chronic coronary syndrome

Abstract: Background Coronary microvascular dysfunction (CMD) is common and is associated with unfavorable cardiovascular events in patients with diabetes mellitus (DM). Coronary angiography-derived index of microcirculatory resistance (caIMR) is a recently developed wire- and hyperemic agent-free method to assess CMD. We aimed to investigate the prognostic impact of CMD assessed by caIMR on clinical outcomes in patients with DM and chronic coronary syndrome (CCS). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Coronary microvascular dysfunction (CMD) may result in reduced coronary flow and vasodilatory capacity, increasing the chance of generating falsely negative FFR values [ 26 ]. Another study by Zhang et al [ 27 ] investigated micro-vascular function in diabetic patients with chronic coronary syndromes, using a novel coronary angiography-derived index of microcirculatory resistance (ca-IMR). This study showed a significantly higher incidence of CMD among diabetic patients, and also showed that CMD is an independent predictor of MACE among diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary microvascular dysfunction (CMD) may result in reduced coronary flow and vasodilatory capacity, increasing the chance of generating falsely negative FFR values [ 26 ]. Another study by Zhang et al [ 27 ] investigated micro-vascular function in diabetic patients with chronic coronary syndromes, using a novel coronary angiography-derived index of microcirculatory resistance (ca-IMR). This study showed a significantly higher incidence of CMD among diabetic patients, and also showed that CMD is an independent predictor of MACE among diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neng et al found that CMD diagnosed by caIMR was a strong predictor for cardiac death and heart failure in CAD patients [ 6 ]. We recently found that CMD measured by caIMR was common and was a reliable predictor of clinical outcomes in diabetic patients with CCS [ 31 ]. Based on this, CMD is clearly associated with poor prognosis, and the identification of predictive factors associated with CMD may be necessary for prompt risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Because the total number of CMD in the nonobstructive group was relatively small, the prognostic effect of CMD in the nonobstructive was inconclusive; thus, further studies with a larger sample are needed to verify our findings. CMD is common among diabetic 44 and prediabetic patients 45 . Diabetes is associated with an increased risk of adverse outcomes in patients with nonobstructive and obstructive acute MI 46,47 .…”
Section: Discussionmentioning
confidence: 99%